Novel voltage Multiplier/Divider-based active square law detector for heartbeat measurement - Šotner, Roman; Polák, Ladislav; Jeřábek, Jan; Langhammer, Lukáš; Freeborn, Todd (ELSEVIER SCI LTD, 2024)
This paper describes a novel active voltage detector that is capable of processing analog signals with levels from units of mV up to 250 mV. An advantage of the proposed circuit is that the relationship between output voltage and input level is not linear but quadratic, which increases the sensitivity when processing low-level signals. The presented solution has tuning parameters for correction or intentional shift of internal DC offset and electronic control of the output signal gain level. The application example presents detection of beats per minute (BPM) in the range of 6-300 BPM, which corresponds to a frequency range of 0.1-5 Hz. The advantage of the presented solution is that the output of the circuit is directly a digital signal compatible with TTL levels, so there is no need for any analog to digital converter to produce a digital signal for further processing.

This paper describes a novel active voltage detector that is capable of processing analog signals with levels from units of mV up to 250 mV. An advantage of the proposed circuit is that the relationship between output voltage and input level is not linear but quadratic, which increases the sensitivity when processing low-level signals. The presented solution has tuning parameters for correction or intentional shift of internal DC offset and electronic control of the output signal gain level. The application example presents detection of beats per minute (BPM) in the range of 6-300 BPM, which corresponds to a frequency range of 0.1-5 Hz. The advantage of the presented solution is that the output of the circuit is directly a digital signal compatible with TTL levels, so there is no need for any analog to digital converter to produce a digital signal for further processing.
Novel voltage Multiplier/Divider-based active square law detector for heartbeat measurement
Keywords: Analog multiplier; Beats per minute (BPM); Detector; Heart rate; Sensing readout; Schmitt comparator; Variable gain amplifier; Analog multiplier; Beats per minute (BPM); Detector; Heart rate; Sensing readout; Schmitt comparator; Variable gain amplifier